Poverty Alleviation Policies - Basrowi, Basrowi; Maulana, Ahmad; Handayani, Wiwik; A. F, Nasywa Roudhotul (LPPM Universitas Bina Bangsa, 2024)
Poverty remains a critical issue in Indonesia, requiring comprehensive and effective policies for its alleviation. This study examines the strategies and implementation of poverty alleviation policies in Indonesia, focusing on their design, impact, and challenges. The study explores various initiatives, including the e-Warong program in Padang, community-based empowerment programs in Papua, and fiscal policy interventions like the Family Hope Program (PKH). Findings reveal that education, healthcare access, and community empowerment play pivotal roles in reducing poverty. However, regional disparities and limited resources remain significant barriers